Garis panduan penyediaan dokumen demonstrasi operasi selamat (penstoran gas petroleum cecair di dalam selinder) (Jabatan Keselamatan dan Kesihatan Pekerjaan, 2001)
This guideline is to clarify and detailed out requirements ofRegulation 10, Occupational Safety and Health (Control of Industrial Major Accident Hazards Regulations 1996 which needs to be followed by the non-major Hazard Installation in preparing the Safe Demonstration Operation Document